Complexities of One-Component Phase Diagrams - Ciccioli, A.; Glasser, Leslie (American Chemical Society, Division of Chemical Education, 2011)
For most materials, the solid at and near the triple-pointtemperature is denser than the liquid with which it is in equilibrium.However, for water and certain other materials, the densities of the phases are reversed, with the solid being less dense. The profound consequences for the appearance of the pVT diagram of one-component materials resulting from such 'anomalous' volume changes in solid liquid transitions are discussed. We discuss and illustrate how the 3DpVT phase diagram changes for this case. A more complex case occurs in systems where the solid liquid field displays continuous density reversal at high pressure, making the phase diagrams of some elements unexpectedly complex. The controversial case of graphite is presented as an example of the difficulties of interpretation. A current version of the carbon pT phase diagram is provided, in a 2DpT representation as well asin a virtual 3D version. The phase diagram of sodium, newly determined to extremely high pressures and illustrated here, shows both melting maxima and minima as well as a number of phase transitions as pressure increases.